2004
DOI: 10.1162/0898929042304732
|View full text |Cite
|
Sign up to set email alerts
|

The Faces of Development: A Review of Early Face Processing over Childhood

Abstract: The understanding of the adult proficiency in recognizing and extracting information from faces is still limited despite the number of studies over the last decade. Our knowledge on the development of these capacities is even more restricted, as only a handful of such studies exist. Here we present a combined reanalysis of four ERP studies in children from 4 to 15 years of age and adults (n = 424, across the studies), which investigated face processing in implicit and explicit tasks. We restricted these analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
259
8
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(315 citation statements)
references
References 88 publications
45
259
8
3
Order By: Relevance
“…The development of the electrophysiological patterns in the P1-N1 time-window from school-age children to adolescence or to early adulthood is not specific to picture naming, as it has been reported in picture categorisation tasks (Batty and Taylor, 2002) as well as with other visual stimuli, such as faces (Taylor et al, 2004) and words (Brem et al, 2006(Brem et al, , 2010. Changes have been associated with expertise and the automatisation of the identification of visual stimuli and their corresponding concepts as well as with the maturation of occipital areas.…”
Section: The Dynamics Of Development In Single Word Planningmentioning
confidence: 88%
See 1 more Smart Citation
“…The development of the electrophysiological patterns in the P1-N1 time-window from school-age children to adolescence or to early adulthood is not specific to picture naming, as it has been reported in picture categorisation tasks (Batty and Taylor, 2002) as well as with other visual stimuli, such as faces (Taylor et al, 2004) and words (Brem et al, 2006(Brem et al, , 2010. Changes have been associated with expertise and the automatisation of the identification of visual stimuli and their corresponding concepts as well as with the maturation of occipital areas.…”
Section: The Dynamics Of Development In Single Word Planningmentioning
confidence: 88%
“…3), along with higher amplitudes and a shift of the P100 peak for children. A decrease in the amplitudes of VEP with age has been repeatedly described using different kinds of visual stimuli (Allison et al, 1984;Brecelj et al, 2002;Hoffmann et al, 2001;Holcomb, Coffey and Neville, 1992;Mahajan and McArtur, 2012;Taylor et al, 2004). Larger amplitudes in children have been attributed to less thick skulls or to generators being closer to the surface electrode in smaller brains (Chauveau et al, 2004;Picton and Taylor, 2007).…”
Section: P1-n1 Range: Pre-linguistic Processesmentioning
confidence: 89%
“…The adult occipitotemporal cortex shows letter-string and face-sensitive responses with identical timing Tarkiainen et al, 2002). The facesensitive response has been detected also in children, but it shows strong maturational changes in timing during childhood and adolescence (Taylor et al, 2004). An EEG study in children (8 -10 years) reported early visual analysis at 155 ms and face-sensitive analysis at 223 ms (Henderson et al, 2003), thus clearly later than in adults and in agreement with our present findings on letterstring analysis.…”
Section: Occipitotemporal Letter-string-sensitive Responses In Childrenmentioning
confidence: 98%
“…The test images are morphs of six different individuals with the target face. Each combination of target and test faces are presented once upright and once inverted, allowing to assess presence of the "face inversion" effect (i.e., better performance for upright than for inverted faces), that is robust in normal adults (Yovel and Duchaine, 2006) and typically developed children (Taylor et al, 2004), but is lacking in patients with acquired prosopagnosia (Farah et al, 1995b) and DP (Schmalzl et al, 2009). Scores for each item are computed by summing the deviations from the correct position for each face.…”
Section: Follow-upmentioning
confidence: 99%